[PP.12.03] EFFECTS OF LOSARTAN ON PROSTANOIDS RELEASE IN TWO MODELS OF METABOLIC ALTERATION IN THE RAT. (September 2017) - Puyó, A.; Lee, H.; Cantu, S.; Donoso, A.; Choi, M.; Peredo, H.
Abstract : Objective: Fructose-overload and high-fat diet in rats are experimental models that resemble human metabolic syndrome. This multifactorial alteration is associated to hypertension. The systemic renin-angiotensin system plays an important role in the regulation of vascular tone. Prostanoids (PR) are endogenous substances derived from arachidonic acid via the cyclooxygenases with vasoactive effects. The aim of this study was to analyze the effects of losartan (L, angiotensin 1 receptor antagonist) on prostanoids (PR) release by the mesenteric vascular bed (MVB) in both models of dietary alteration. Design and method: Six groups (n = 6) of male Sprague-Dawley rats were studied during 9 weeks: Control (C), standard diet (SD) and tap water to drink; fructose-overloaded (F), SD and fructose solution (10% W/V) to drink; HF diet (HF), 50% (w/w) bovine fat added to SD and tap water; C + L (CL), SD + 30 mg/Kg/day L in the drinking water; F + L (FL) 30 mg/Kg/day L in the fructose solution; and HF + L (HFL) 30 mg/Kg/day L in the drinking water. MVBs were removed and incubated and the released PRs measured by HPLC. Results: F and HF increased systolic blood pressure (SBP, mmHg, 133 ± 3, 145 ± 5 vs. C: 116 ± 2, p < 0.01 and p < 0.001). In the FL and HFL groups, L decreased SBP (102 ± 5 vs. F, 111 ± 3 vs. HF, p < 0.001 and p < 0.01). F diminished prostaglandin (PG) 6-ketoF1alpha, stable metabolite of the vasodilator prostacyclin (PGI2), (ng PR/mg tissue, 58 ± 11 vs. C: 98 ± 8, p < 0.05); and PGE2 (ng/mg, 35 ± 7 vs. C: 87 ± 6, p < 0.01). HF diet increased thromboxane (TX) B2, stable metabolite of the vasoconstrictor TXA2, (ng PR/mg tissue, 111 ± 5 vs. C: 64 ± 7, p < 0.001); and PGF2alpha (150 ± 10 vs. C: 83 ± 8, p < 0.01). In the FL group, L increased PG6-ketoF1alpha (117 ± 10 vs. F, p < 0.05) and PGE2 (104 ± 11 vs. F, p < 0.01). In the HFL group, L decreased TXB2 (66 ± 7 vs. HF, p < 0.01); and PGF2alpha (90 ± 7 vs. HF, p < 0.05). Conclusions: In conclusion, one of the possible mechanisms by which L reduced blood pressure in these models could be an improvement of endothelial function through a regulation of PR release which produced a decrease in vasoconstriction.